2005
DOI: 10.1111/j.1532-950x.2005.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser Fenestration of the Mesial Septum for Treatment of Guttural Pouch Chondroids in a Pony

Abstract: When guttural pouch empyema and/or chondroids is associated with adhesion of the pharyngeal ostium, laser fenestration of the mesial septum from the opposite guttural pouch should be considered as an alternative approach for access, rather than classic external surgical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
0
19
0
1
Order By: Relevance
“…The endoscopic procedure does not require general anaesthesia for the patient, avoiding the complications often described for the other techniques (Gehlen and Ohnesorge, 2005), and it provides an easier and safer approach to the lesion compared with traditional methods. It is the authors' opinion that the good outcome observed in this clinical case was also due to the short period which had elapsed between the development of the stenosis and its diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The endoscopic procedure does not require general anaesthesia for the patient, avoiding the complications often described for the other techniques (Gehlen and Ohnesorge, 2005), and it provides an easier and safer approach to the lesion compared with traditional methods. It is the authors' opinion that the good outcome observed in this clinical case was also due to the short period which had elapsed between the development of the stenosis and its diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopic approach to guttural pouches is easy to perform but it may be obstructed when stenotic or fibrotic processes have occurred in the pharyngeal orifice. Stenosis of the pharyngeal orifice has been described in a few papers (Gehlen and Ohnesorge, 2005;Perkins et al, 2006). It is not a common disease but may complicate the treatment of empyema and it must be resolved in order for there to be complete recovery from pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In guttural pouch tympany, redundant mucosal tissue of the plica salpingopharyngeus (salpingopharyngeal fold) of the nasopharyngeal orifice of the Eustachian tube can act as a one‐way valve causing air retention in the guttural pouch . Treatment of guttural pouch tympany includes fenestration of the median septum, enlargement of the nasopharyngeal orifice, or resection of the salpingopharyngeal fold . The tensor veli palatini muscles contract facilitating opening of the nasopharyngeal cartilage of the guttural pouch during swallowing .…”
mentioning
confidence: 99%